ANALISIS GILIR BICARA DALAM TUTURAN LISAN PADA PEMBELAJARAN TEKS EDITORIAL DI SMK MUHAMMADIYAH 2 GENTENG - Dian Islamiyah; Gigit Mujianto (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study has four objectives, namely 1) describing the forms and characteristics of spoken language variations, 2) explaining linguistic and non-linguistic elements in spoken language variations, 3) explaining the stages of spoken language variations, and 4) describing the form of conversational structures related to functional models. take turns talking in learning at SMK Muhammadiyah 2 Genteng. To answer the problems formulated by the researchers, it was carried out using the theory of variations in spoken language with the functional method of speech rotation. This research belongs to the type of descriptive research with qualitative analysis data processing techniques. Data and Sources of data in this study in the form of transcripts of learning activities carried out by teachers and students who are in progress. The results of the research obtained are that Indonesian Language Learning in the Editorial Text of SMK Muhammadiyah 2 Genteng shows that there is a shift in speech and the use of language variations in the learning process. In the interaction or communication carried out in learning activities, the five structures or organizations of the conversation will be linked, namely speaking shifts, pauses, overlaps, back channels, and agency pairs.